QUALITY OF MALALUGIS SALTED FISH: A TRADITIONAL PRODUCT FROM BEBALANG, SANGIHE ISLANDS - Ansar, Novalina Maya Sari; Ijong, Frans Gruber; Tanod, Wendy Alexander; Cahyono, Eko; Rieuwpassa, Frets Jonas; Mandeno, Jefri Anthonius; Sambeka, Yana (Chanos Chanos, 2024)
Bebalang Village is located in South Manganitu District, Sangihe Islands Regency, North Sulawesi. Bebalang Village is surrounded by the sea, so there are many coral reefs as a place for fish to live. Bebalang Village has huge fisheries potential, especially for pelagic fish such as flying fish (Decapterus sp.) with the local name malalugis. Generally, fishermen in Bebalang Village process malalugis fish into salted fish. However, salted fish processing in Bebalang Village still needs to be improved due to a lack of infrastructure, technology, and inadequate knowledge. In addition, sanitation and hygiene during processing could be more optimal, affecting the quality and safety of processed products. This study aims to evaluate the quality of salted fish produced by fishermen in Bebalang Village. The method used in this research is descriptive quantitative. Salted fish test parameters are proximate, salt level, total bacteria and total fungi. Based on the test results of Kampung Bebalang salted fish, the moisture content ranged from 37.31-41.23%; protein ranged from 46.82-50.13%; salt level ranged from 10.66-15.58%; ash content from 12.25-13.58%; total bacteria between 2.6-4.8×103 CFU/gram; and total fungi which ranged from 5.2-9.5×102 CFU/gram.